EKUIVALENSI RING RICKART DAN RING BAER BESERTA *-RINGNYA - hanifah, Hanifah (MATEMATIKA, 2009)
Rickart ring and Baer ring as well as its *-ring are a particular form of ring where its annihillator is generated by an idempotent element or projection. By using concept of annihilator, idempotent, projection and inexistence of zero divisor on ring can be showed equivalent among the rings. Â